A hybrid scoping and systematic review of food safety and quality control in selected low- and middle-income countries: challenges, policies, and effective interventions in Africa, Asia, and Latin America - Arero Dassie, Godana; Dhugassa Girsha, Worku; Kalu Beggi, Sultan (Frontiers in Food Science and Technology, 2025)
BackgroundFood safety is a main community wellbeing concern in developing regions, top to elevated load of food borne illness. Feeble application, execution, obliviousness, and unawareness, and deprived hygiene worsen contagion hazard. In spite of presented intercessions, their efficiency remnants contradictory, reflecting a serious study gap. The objective was to assess vital food safety defy and assess the efficacy of intercessions in developing regions.MethodsA scoping review identified major food safety challenges and policies using peer-reviewed and grey literature from PubMed, Scopus, Web of Science, and Google Scholar. A systematic review assessed intervention effectiveness using PRISMA guidelines. A total of 3,500 articles were screened, with 220 meeting the inclusion criteria. Findings included contamination rates and regulatory enforcement levels. Logical outcomes incorporated interferences efficiency with adjusted odds ratios (AORs) and 95% confidence intervals for a variety factors.FindingsA scoping review showed numerous significant variables determining food safety results. Almost partly of the incorporated investigations (45%) verified pathogen infestation, within unofficial marketplace. Whereas 60% showed feeble food safety inspection, and hygiene control. Lack of consumers understanding was as well well-known in 50% of survey. Systematic review outcomes revealed that the performance of Hazard Analysis and Critical Control Points considerably rreduced food borne diseases by 35% (AOR = 0.65, 95% CI: 0.55–0.85). Foodborne illness prevention training was connected with a 40% amplify in falling in line (AOR = 1.4, 95% CI: 1.1–1.7). Access to clean water (AOR = 1.8, 95% CI: 1.3–2.2) and availability of proper sanitation facilities (AOR = 1.6, 95% CI: 1.2–2.0) were both significantly linked to improved food safety practices. Furthermore, government regulatory enforcement emerged as a strong determinant of compliance, with enforcement increasing adherence rates more than twofold (AOR = 2.1, 95% CI: 1.5–2.6).Conclusion and RecommendationHazard Analysis, Critical Control Points, Low- and Middle-Income Countries; Public Health; Regulatory Enforcement; Contamination; Hygiene, training programs, and strong regulatory enforcement significantly enhance food safety. Policy harmonization and infrastructure development are essential for sustainable improvements.